Implementation Plan in Response to Board-Endorsed Recommendations for the IEO Evaluation of Research at the IMF : Relevance and Utilization. (Policy Papers; Policy Paper ;, 2012)
This paper presents a forward-looking implementation plan for the above-cited Independent Evaluation Office (IEO) report. During the Board discussion, Executive Directors noted that the report 'provides a balanced assessment of the quality, relevance, management, and utilization of IMF research' and 'were particularly encouraged by the overall finding that a large number of IMF analytical papers are of high quality, widely read, and appreciated by country authorities and the research community.' At the same time, they noted the finding that 'IMF research is of uneven quality and perceived to be message driven.' Directors therefore saw scope for 'enhancing the relevance and technical quality of the analytical work, openness to alternative points of view, and coordination of research activities across the institution.'.